Revealing taste-based discrimination in hiring: A correspondence testing experiment with geographic variation - Magnus Carlsson; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2011)
The standard correspondence testing experiment does not identify whether employer prejudice drives discriminatory behavior when hiring. This article proposes a new methodology using geographic variation to explore the link between employer attitudes toward ethnic minorities and the ethnic difference in callbacks for a job interview. Using already existing Swedish data we find that a randomly selected employer is more likely to discriminate against a minority job applicant in regions where the average employer has more negative attitudes.
urn:nbn:de:101:1-2012010913732
Keywords: J64; J71; 330; field experiments on hiring; employer discrimination; negative attitudes; regional variation; Personalbeschaffung; Arbeitsnachfrage; Arbeitsmarktdiskriminierung; Ethnische Gruppe; Region; Schweden